Harvesting Hope: Islamic and Catholic Thought Nurturing Agropreneurial Generations for Sustainable Food Security in Indonesia - Triatmo, Agus Wahyu; Husen, Fathurrohman; Triana, Unika (CV. BImbingan Belajar Assyfa, 2024)
This service is based on the urgent need to address the decline in the number of young farmers in Indonesia, which if left unchecked could threaten national food security. This study aims to explore more deeply the potential of Islamic boarding schools in forming agropreneur generations. By using the Participatory Action Research (PAR) method which includes five cycles: knowing, understanding, planning, acting, and changing, this study successfully mapped the potential of Islamic boarding schools. After understanding the potential, an agropreneur education and training program for vegetable and fruit cultivation was implemented. The researchers collaborated with the Wonogiri Agriculture Service as a partner in this study. The subjects of the study included stakeholders of Muhammadiyah Green School Wonogiri, including leaders, religious teachers (Asatiz), and students (Santri). The results of the study showed that the school has the potential for human resources in the form of motivated Santri and Asatiz, as well as natural resources in the form of unused agricultural land. The Agropreneur Training Program succeeded in fostering motivation among the Santri to be involved in the entire agricultural process, from planting to harvesting, as evidenced by their active participation. Cognitively, both Santri and Asatiz understand the process of planting, plant care, harvesting, and processing the results. The benefit for Islamic boarding schools is that some of their food needs can be met through the empowerment of these agropreneur students.